Teaching Dubbing Translation in Indonesian Classroom: Benefits and Challenges - Niken Paramita (Universitas Putra Indonesia YPTK Padang, 2022)
Currently, dubbed version of imported films or programs are available as one of the options of content localization, aside from subtitles. Despite the potential of dubbing and dubbing translation, especially in Indonesia, not many departments in higher education institutions offer lesson in dubbing translation. This article aims to propose what topics can be covered in a dubbing translation lesson, why dubbing translation lesson is important, and what dilemmas arise in teaching dubbing translation. The study was conducted using literature review method. Future research may be done to find the gap between the translation skills required in Indonesian dubbing industry and the ones acquired by Translation students in Indonesia